Financial consumers protection regime in Malaysia: main guidelines issued by Bank Negara Malaysia - Hassan, Rusni; Mohamad, Nurun Nadia (New Millennium Discoveries, UK, 2019)
The purpose of this paper is to discuss the financial consumer protection in Islamic banks in the context of Islamic Financial Service Act 2013 (IFSA 2013) by looking simultaneously to the standards and guidelines issued by Bank Negara Malaysia (BNM). This conceptual paper examines relevant provisions in both Acts as well as in respective standards and guidelines by BNM related to financial consumer protection. In keeping with the main focuses of BNM on promoting fair, responsible and professional conduct by financial services providers to secure financial stability, this paper highlights the provisions which need to be adhered by the Islamic banks in treating their financial consumers. The discussions of the relevant provisions, standards, and guidelines will enrich the academic understanding of financial consumer protection in Malaysia. This study provides an insight on the initiatives taken in Malaysia particularly in the Islamic banking industry to protect the financial consumers.